(12x+10)-(-4x-6x+10)=

Simple and best practice solution for (12x+10)-(-4x-6x+10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x+10)-(-4x-6x+10)= equation:


Simplifying
(12x + 10) + -1(-4x + -6x + 10) = 0

Reorder the terms:
(10 + 12x) + -1(-4x + -6x + 10) = 0

Remove parenthesis around (10 + 12x)
10 + 12x + -1(-4x + -6x + 10) = 0

Reorder the terms:
10 + 12x + -1(10 + -4x + -6x) = 0

Combine like terms: -4x + -6x = -10x
10 + 12x + -1(10 + -10x) = 0
10 + 12x + (10 * -1 + -10x * -1) = 0
10 + 12x + (-10 + 10x) = 0

Reorder the terms:
10 + -10 + 12x + 10x = 0

Combine like terms: 10 + -10 = 0
0 + 12x + 10x = 0
12x + 10x = 0

Combine like terms: 12x + 10x = 22x
22x = 0

Solving
22x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '22'.
x = 0

Simplifying
x = 0

See similar equations:

| 6[-6x+6+4x(x+1)]=6x+2 | | 0.5x+0.25=x | | 3x+3(5x-10)=138 | | (2mn+8m^2n-5n+6m)= | | 0=(t-20)+(t-400) | | 8.57x+17.14=34.28 | | t-20=t-400 | | (2mn+8m^2n-5n+6m)(10mn^2)= | | 3cos(x)=8-4sec(x) | | Y=2500-2x | | 10x+4x+4+9=4x+3+9x | | x^2+4x=47 | | 3.91x+16=15.2881+4x | | 3cosx=8-4secx | | v^2=18v | | -5(4b+4)+(21b-7)=0 | | R^2-4r-6=0 | | (x^2-10x)+(y^2-6y)=-33 | | y(-2)=-6.8(-2)+5 | | 3x+4(2x-12)=73 | | 5y+18y-(-2y)+(-10y)= | | 0.12=0.5y | | 0.12=0.5 | | 5m-7=12 | | 4p-8p=16 | | 3(2y-0.3)=19.4-9 | | 8x+9y=-10 | | 4y-17=90 | | 2x+x^2-59=0 | | 7y+8=90 | | -5b+21=8b-3(b-7) | | 5x+5(2x-12)=30 |

Equations solver categories